THE ROLE AND IMPACT OF TASK-BASED LANGUAGE TEACHING ON LINGUISTIC AND COMMUNICATIVE COMPETENCE OF FUTURE FOREIGN LANGUAGE TEACHERS (Web of Teachers: Inderscience Research, 2025)
This article explores the role and impact of Task-Based Language Teaching (TBLT) in enhancing the linguistic and communicative competence of future foreign language teachers. In response to the increasing demands of globalized education, language educators must develop not only theoretical knowledge but also practical, context-sensitive communicative skills. TBLT presents a dynamic framework wherein learners engage in meaningful, task-oriented activities that mirror real-world communication. Drawing upon established theories in second language acquisition, empirical studies, and pedagogical models, this article demonstrates how TBLT significantly contributes to the integrated development of linguistic and communicative competences in pre-service teacher education. Practical implications for curriculum design, teacher training programs, and future research directions are provided.